2005
DOI: 10.1063/1.1849418
|View full text |Cite
|
Sign up to set email alerts
|

Tunneling effects and intersubband absorption in AlN/GaN superlattices

Abstract: We report on intersubband absorption and photovoltage measurements on regular GaN/AlN-based superlattice structures. For barrier thicknesses larger than about 25 Å, the optical intersubband absorption peaks at a considerably smaller energy than the photovoltage spectrum. A simple model taking into account the oscillator strength of the involved transitions and the corresponding tunneling probabilities agrees with the experimental findings. According to this model, the observed photovoltage is the macroscopic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…13. In this experiment, three different samples with 3 QW thicknesses were grown; this resulted in a series of photodetectors being sensitive between 2.33 and 1.49 "m [47]. As mentioned in the Introduction, it was only in 2007 when the functioning of these devices could be explained in a satisfactory way.…”
Section: B Photodetectorsmentioning
confidence: 99%
“…13. In this experiment, three different samples with 3 QW thicknesses were grown; this resulted in a series of photodetectors being sensitive between 2.33 and 1.49 "m [47]. As mentioned in the Introduction, it was only in 2007 when the functioning of these devices could be explained in a satisfactory way.…”
Section: B Photodetectorsmentioning
confidence: 99%
“…The existence of defects such as charge traps and screw dislocations has led to the need for systematic verification of the origin of negative differential resistance (NDR) features. [13][14][15][16][17] Another important characteristic of AlGaN/GaN heterostructures is the large built-in electrostatic fields due to both spontaneous and piezoelectric polarization which alter the current-voltage (I-V) characteristics significantly. Recent advances in growth technology have reduced threading dislocation densities substantially to allow repeatable measurement of wurtzite and cubic AlGaN RTDs [18][19][20][21][22][23] and sequential tunneling devices.…”
Section: Introductionmentioning
confidence: 99%
“…As pointed out by Baumann et al, [2] in the majority of the experiments, the effects were observed purely optically [3] and no vertical current transport was demonstrated. Just a few studies to our knowledge were reported on vertical current transport through thin AlN barriers in a resonant tunneling diodes [4,5].…”
mentioning
confidence: 77%